2003
DOI: 10.1242/jeb.00338
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines as olfactory stimuli in the goldfish Carassius auratus

Abstract: SUMMARY Electrophysiological responses of goldfish olfactory receptor neurons(ORNs) and goldfish behavioral responses to polyamines were investigated in vivo. Electro-olfactogram (EOG) recordings indicated that polyamines (putrescine, cadaverine and spermine) are potent olfactory stimuli for goldfish with estimated electrophysiological thresholds of 10–8–10–7 mol l–1,similar to that for L-arginine, the most stimulatory amino acid. Although thresholds were similar, the magnitude of the EOG respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 58 publications
5
92
1
5
Order By: Relevance
“…Receptor affinities can be much lower in heterologous systems than in vivo (28)(29)(30), where expression of receptors and signaling components are presumably optimized. Nevertheless, the threshold of cadaverine detection by TAAR13c of 3 μM is very similar to in vivo thresholds observed for the intact olfactory system (6,31) and to thresholds measured for isolated olfactory sensory neurons (2). Although it is difficult to estimate naturally occurring cadaverine concentrations close to dead fish, the cadaverine concentration we measured in rotten zebrafish extracts was several orders of magnitude higher than the TAAR13c activation threshold, and presumably high enough to allow detection of that odor source from some distance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Receptor affinities can be much lower in heterologous systems than in vivo (28)(29)(30), where expression of receptors and signaling components are presumably optimized. Nevertheless, the threshold of cadaverine detection by TAAR13c of 3 μM is very similar to in vivo thresholds observed for the intact olfactory system (6,31) and to thresholds measured for isolated olfactory sensory neurons (2). Although it is difficult to estimate naturally occurring cadaverine concentrations close to dead fish, the cadaverine concentration we measured in rotten zebrafish extracts was several orders of magnitude higher than the TAAR13c activation threshold, and presumably high enough to allow detection of that odor source from some distance.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with electrophysiological studies indicating limited cross-adaptation of olfactory responses to cadaverine and putrescine (2). Here, we identified TAAR13c as a highly sensitive detector of odd-chained diamines that include the repulsive odor cadaverine.…”
Section: Cadaverine and Other Diamines Activate Sparse Olfactory Sensorysupporting
confidence: 91%
See 1 more Smart Citation
“…The current study is the first to demonstrate cross-adaptation between calcium and a second odourant. Cross-adaption has been seen in fish for other stimuli such as polyamines, bile salts and amino acids, but not calcium (Hansen et al, 2003;Michel et al, 2003;Rolen et al, 2003). A study by Hubbard et al (2002) showed that removal of calcium from the surrounding water for goldfish resulted in a small, but significant, increase in response to L-serine.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that this decrease in response may be due to cross-adaptation between calcium and L-arginine. Cross-adaptation occurs when two odourants have an overlap in the OSNs that recognize each odourant individually, such that when the OE is stimulated by one of the odourants, OSNs that would normally respond to the second odourant cannot respond to a second stimulus because they are already activated by the first odourant (Hansen et al, 2003;Michel et al, 2003;Rolen et al, 2003). Cross-adaptation, therefore, results in a reduced olfactory response to a second odourant after a first odourant has already activated OSNs required to perceive the second odourant.…”
Section: Introductionmentioning
confidence: 99%